1996
DOI: 10.3168/jds.s0022-0302(96)76528-1
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal Degradation, Amino Acid Composition, and Intestinal Digestibility of the Residual Components of Five Protein Supplements

Abstract: Two ruminally cannulated Holstein cows (approximately 202 DIM) were used to determine the in situ degradability of five protein supplements: blood meal, meat and bone meal, corn gluten meal, expeller soybean meal, and solvent extracted soybean meal. Dacron bags containing 4 g of each supplement in duplicate were soaked in water and then incubated in the rumen for 0, 3, 6, 12, 18, and 24 h for 3 d. Four extra sample bags of each supplement were incubated in the rumen for 12 h to determine the in vitro intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
16
4
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 15 publications
8
16
4
2
Order By: Relevance
“…Cozzi et al [4] only studied the essential amino acids and recorded an apparent higher degradability for histidine, arginine and lysine in agreement with the present results. In the same manner, the degradation of branchedchain amino acids, lower than that of TAA showed in this study was also observed in many works [5,9,13,20,27] carried out with punctual incubations. from the rumen with the liquid phase of a part of the soluble proteins.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Cozzi et al [4] only studied the essential amino acids and recorded an apparent higher degradability for histidine, arginine and lysine in agreement with the present results. In the same manner, the degradation of branchedchain amino acids, lower than that of TAA showed in this study was also observed in many works [5,9,13,20,27] carried out with punctual incubations. from the rumen with the liquid phase of a part of the soluble proteins.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, available information concerning rumen degradation of their amino acids is abundant. Most published results only refer to a few incubation times [5,8,13,16,20,27,32]. However, studies that measured degradability values are limited [4,9,30], and only that of Harstad and Prestløken [9] provided full information about degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Including whey in a total mixed diet or ensiling whey has been shown to improve the digestibility of high fiber feed (Schingoethe 1976;Thivend 1977). Dried whey has been added to the diet to increase ruminal fermentation and microbial protein synthesis (Maiga et al 1996) as it contains 37-72% lactose (Maiga et al 1995). Whey adds fermentation stimulants such as bacteria enzymes and nutrients, but is not recommended that it be ensiled with high moisture feeds (Alberta Agriculture Food and Rural Development 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Ruminal amino acid degradation of DDGS Although DDGS may be considered as a good source of UDP, the PPS values showed that ID of UDP may be low compared with soya bean meal and corn gluten meal (Maiga et al, 1996;Kleinschmit et al, 2007) but can be higher than the rapeseed meal (Steingass et al, 2013). The PPS of DDGSs was higher than from DDGS-r, and they were low correlated with each other.…”
Section: Discussionmentioning
confidence: 95%